2000
DOI: 10.1207/s15324826an0701_3
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Fluency and Repetition Skills in Healthy Older Spanish-English Bilinguals

Abstract: The influence of bilingualism on cognitive test performance in older adults has received limited attention in the neuropsychology literature. The aim of this study was to examine the impact of bilingualism on verbal fluency and repetition tests in older Hispanic bilinguals. Eighty-two right-handed participants (28 men and 54 women) with a mean age of 61.76 years (SD = 9.30; range = 50-84) and a mean educational level of 14.8 years (SD = 3.6; range 2-23) were selected. Forty-five of the participants were Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
175
6
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(210 citation statements)
references
References 16 publications
26
175
6
3
Order By: Relevance
“…Bilingualism also incurs some nonlinguistic processing advantages (e.g., bilingualism protects against age-related decline in cognitive control; Bialystok et al, 2004). However, bilingualism also entails some processing costs, including reduced verbal fluency scores (Gollan et al, 2002;Rosselli et al, 2000) and lower BNT scores (Roberts et al, 2002). The current study suggests that older adults' naming skills are similarly affected by bilingualism as younger adults (Kohnert et al, 1998) and build on previously reported bilingual effects by suggesting that there is no "magic point" at which speakers become bilingual.…”
Section: Discussionsupporting
confidence: 68%
“…Bilingualism also incurs some nonlinguistic processing advantages (e.g., bilingualism protects against age-related decline in cognitive control; Bialystok et al, 2004). However, bilingualism also entails some processing costs, including reduced verbal fluency scores (Gollan et al, 2002;Rosselli et al, 2000) and lower BNT scores (Roberts et al, 2002). The current study suggests that older adults' naming skills are similarly affected by bilingualism as younger adults (Kohnert et al, 1998) and build on previously reported bilingual effects by suggesting that there is no "magic point" at which speakers become bilingual.…”
Section: Discussionsupporting
confidence: 68%
“…In one study, college-aged Spanish-English bilinguals produced significantly fewer correct responses in 9 of 12 semantic categories (with trends in the same direction in 2 of the 3 remaining categories) and 6 of 10 letter categories, and the difference between participant groups was larger and more robust on semantic categories (Gollan, Montoya, & Werner, 2002). Similarly, in a study of healthy older adults, Spanish-English bilinguals produced fewer correct responses, relative to monolinguals, in 2 semantic, but not in 2 letter, categories that were tested (only 4 categories total were tested in this study; Rosselli et al, 2000). As was described earlier regarding increased TOT rates in bilinguals, the lower verbal fluency scores in both studies could not be attributed solely to language dominance; bilinguals produced fewer correct responses even when they were tested exclusively in their dominant language.…”
supporting
confidence: 49%
“…However, evidence suggests that maintaining more than one language in a single cognitive system introduces some subtle but significant processing costs. When compared to their monolingual peers, bilinguals have more tip-of-the-tongue or TOT retrieval failures (Gollan & Acenas, 2004;Gollan, Bonanni, & Montoya, 2005;Gollan & Silverberg, 2001, but see Gollan & Brown, 2006), have reduced category fluency (Gollan, Montoya, & Werner, 2002;Portocarrero, Burright, & Donovick, 2007;Rosselli et al, 2000), name pictures more slowly (Gollan, Montoya, Fennema-Notestine, & Morris, 2005), and name fewer pictures correctly on standardized naming tests such as the Boston Naming Test (Kohnert, Hernandez, & Bates, 1998;Roberts, Garcia, Desrochers, & Hernandez, 2002;Gollan, Fennema-Notestine, Montoya, & Jernigan, 2007). Importantly, bilingual naming disadvantages were found even when bilinguals were tested exclusively in their dominant language (e.g., Gollan & Acenas, 2004;, and more recently in bilinguals who are dominant in their first-learned language (Ivanova & Costa, in press; many of the bilinguals in the studies by Gollan et al, were dominant in their secondlearned language).…”
mentioning
confidence: 99%